2015
DOI: 10.3168/jds.2014-9068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilization rate and regrowth interval of grass herbage on methane emission of zero-grazing lactating dairy cows

Abstract: Dairy cattle farming in temperate regions often relies on grass herbage (GH)-based diets but the effect of several grass management options on enteric CH4 emission has not been fully investigated yet. We investigated the combined effect of N fertilization rate and length of regrowth period of GH (predominantly ryegrass) on CH4 emission from lactating dairy cows. In a randomized block design, 28 lactating Holstein-Friesian dairy cows received a basal diet of GH and compound feed [85:15; dry matter (DM) basis]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
18
2
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 26 publications
13
18
2
13
Order By: Relevance
“…This may explain the relatively small amount of CH 4 per unit of FPCM with LF grass silage and, thus, explain the similar CH 4 emission levels between N fertilisation rates in the present study in contrast to the differences simulated by Bannink et al (2010). Grass silage quality effects described in the present study were generally in line with those observed for dairy cows offered grass herbage under zero-grazing conditions (Warner et al, 2015). Increasing the grass maturity from 3 to 5 weeks of regrowth increased CH 4 per unit of FPCM by 14%, whereas increasing the N fertilisation rate from 20 to 90 kg of N/ha did not affect CH 4 emissions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This may explain the relatively small amount of CH 4 per unit of FPCM with LF grass silage and, thus, explain the similar CH 4 emission levels between N fertilisation rates in the present study in contrast to the differences simulated by Bannink et al (2010). Grass silage quality effects described in the present study were generally in line with those observed for dairy cows offered grass herbage under zero-grazing conditions (Warner et al, 2015). Increasing the grass maturity from 3 to 5 weeks of regrowth increased CH 4 per unit of FPCM by 14%, whereas increasing the N fertilisation rate from 20 to 90 kg of N/ha did not affect CH 4 emissions.…”
Section: Discussionsupporting
confidence: 84%
“…Increasing the grass maturity from 3 to 5 weeks of regrowth increased CH 4 per unit of FPCM by 14%, whereas increasing the N fertilisation rate from 20 to 90 kg of N/ha did not affect CH 4 emissions. The grass silages tested in the present study generated 8% more daily CH 4 per cow than the grass herbage tested by Warner et al (2015). Nonetheless, emitted CH 4 per unit of FPCM was slightly lower (−4%) in the present study due to a considerably larger milk production (+16%) realised with grass silage at comparable DMI levels.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Consequently, changes in grass total N concentration on this site may be relatively less responsive to divergent inorganic fertilizer N application rates (Keating & O'Kiely, ). Nevertheless, the magnitude of difference obtained for the grass CP concentration is comparable to that reported by Peyraud et al () (44 g/kg DM), Hennessy, O'Donovan, French, and Laidlaw () (39 g/kg DM: autumn) and Warner et al () (61 g/kg DM) for L. perenne ‐dominant swards that received inorganic fertilizer N application rates of 0 or 80 kg/ha (per cut), 5 or 50 kg/ha (per 4 week rotation) and 20 or 90 kg fertilizer N/ha respectively. In the current experiment, an increase in CP concentration of 10 g/kg DM was associated with a decrease in WSC concentration of 14.8 g/kg DM.…”
Section: Discussionsupporting
confidence: 85%
“…In vivo measurements confirm the merit of adopting a more dynamic approach as it demonstrates the limiting effect of N supply on rumen fiber digestion at similar crude protein contents in dietary DM. A crude protein level of 11.5% in maize silage diets was tested by Spek et al (2013) and a level of 10.3% in grass herbage diets was tested by Warner et al (2015), which in both studies resulted in a rumen ammonia concentration below 2 mM which is considered to be well below critical levels for ensuring optimal microbial activity (Dijkstra et al, 1998). The static model calculated a rumen protein balance of around zero at this low protein level (Spek et al, 2013), hence falling within recommendations.…”
Section: Introductionmentioning
confidence: 99%